2015
DOI: 10.1038/ncomms8534
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective biosynthetic pathway to non-natural C50 carotenoids assembled from moderately selective enzymes

Abstract: Synthetic biology aspires to construct natural and non-natural pathways to useful compounds. However, pathways that rely on multiple promiscuous enzymes may branch, which might preclude selective production of the target compound. Here, we describe the assembly of a six-enzyme pathway in Escherichia coli for the synthesis of C50-astaxanthin, a non-natural purple carotenoid. We show that by judicious matching of engineered size-selectivity variants of the first two enzymes in the pathway, farnesyl diphosphate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 46 publications
0
49
0
Order By: Relevance
“…by higher copy numbers of HvCHS2 . A similar strategy of using enzymes as filters for selective production of the compound of interest was recently used in E. coli for unnatural C50 carotenoids (Furubayashi et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…by higher copy numbers of HvCHS2 . A similar strategy of using enzymes as filters for selective production of the compound of interest was recently used in E. coli for unnatural C50 carotenoids (Furubayashi et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Furubayashi et al designed an unnatural biosynthetic route toward C 50 -astaxanthin which has stronger antioxidant property than the natural C 40 -astaxanthin (Figure 5a). [46] For C 50 -astaxanthin biosynthesis, farnesyl diphosphate (FPP) should be first converted to a C 25 precursor. The authors brought FPP synthase from Geobacillus stearothermophilus and performed site-directed mutagenesis to synthesize C 25 PP.…”
Section: Enzyme Engineeringmentioning
confidence: 99%
“…As a result, C 50 -astaxanthin could be successfully produced in E.coli. [46] For the production of taxol intermediates, many papers have used a biosynthetic route through taxa-4(5)-11(12)-diene, usually known as taxadiene (Figure 4). However, Edgar et al found out that taxadiene is easily degraded after first epoxidation.…”
Section: Enzyme Engineeringmentioning
confidence: 99%
“…pUCara-GES M53 was constructed by PCR-amplifying the reading frame of GES M53 from pUC-GES M53 (Furubayashi et al, 2014) and subcloning it into the EcoRI-ApaI site of the pUCara vector (Furubayashi et al, 2015).…”
Section: Methodsmentioning
confidence: 99%